2021
DOI: 10.1093/treephys/tpab014
|View full text |Cite
|
Sign up to set email alerts
|

Spring phenology is affected by fall non-structural carbohydrate concentration and winter sugar redistribution in three Mediterranean nut tree species

Abstract: Deciduous trees mostly rely on non-structural carbohydrates (NSC—soluble carbohydrates and starch) stored prior to dormancy to sustain both spring bloom and the initial phase of spring growth prior to the transition of leaves from sink to source. Winter management of NSC, their loss due to respiration, reallocation patterns and remobilization during spring, seems to be key to a timely and synchronous bloom. To assess tree dependence on NSC during dormancy, we tested whether the interruption of local branch NSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 51 publications
0
16
1
Order By: Relevance
“…Additionally, there is increasing evidence suggesting that conversions between NSC forms, soluble sugars and starches, may potentially serve as a ‘dormancy clock’ 6 . Hence, the timing and synchrony of bloom is strongly impacted by disturbances especially to the NSC accumulation and dispersion that flank dormancy 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, there is increasing evidence suggesting that conversions between NSC forms, soluble sugars and starches, may potentially serve as a ‘dormancy clock’ 6 . Hence, the timing and synchrony of bloom is strongly impacted by disturbances especially to the NSC accumulation and dispersion that flank dormancy 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, despite the importance of NSC activity in providing protection against adverse weather conditions through dormancy and in influencing the timing and synchrony of bloom, little attention has been given to how trees physiologically prepare for this quintessential period of quiescence 6 , 7 , 9 . The amount of reserves needed to maintain dormancy and a healthy growth resumption (bloom/leafing) can be variable and not easily predicted.…”
Section: Introductionmentioning
confidence: 99%
“…Needle growth of Larix gmelinii in spring drew nearly 50% of the carbohydrates fixed in the previous year 81,82 . Phloem girdling showed that deficient carbon storage can significantly delay the timing of spring budbreak and reduce bud size 27 .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, plants need to assimilate and store sufficient carbohydrates in the preceding growing season to resist to the frost temperatures in winter and support growth reactivation in spring [23][24][25][26] . In temperate regions, nonstructural carbohydrates (NSC; soluble sugar and starch) often reach the maximum levels in autumn before winter dormancy, but become depleted by early summer after spring growth [27][28][29] . Girdling experiments have demonstrated that a later budbreak is often associated with a lower NSC availability 30,31 .…”
Section: Introductionmentioning
confidence: 99%
“…In most deciduous trees, like almonds, carbon is fixed by the leaves during the summer and is stored for the winter, mainly as starch in tree stems and roots. By the end of the winter, trees drop their leaves and rely on their residual carbohydrate resources to fuel bud-break, bloom, and the early stages of vegetative growth (Ito et al, 2012;Tixier et al, 2017Tixier et al, , 2020Fernandez et al, 2018;Amico Roxas et al, 2021). This fuel reservoir is the only energy source for the deciduous tree until new leaves emerge and become fully functional.…”
Section: Introductionmentioning
confidence: 99%